2015
DOI: 10.1007/s12350-014-9949-6
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study testing the effect of physical training over the myocardial perfusion and quality of life in patients with primary microvascular angina

Abstract: Physical training in patients with PMA is associated with reduction of myocardial perfusion abnormalities, increasing of physical capacity, and improvement in QOL. The findings of this hypothesis-generating study suggest that APT can be a valid therapeutic option for patients with PMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Carvalho et al published data from Brazil in 2014 [ 16 ]. Patients were included with exertional CP, normal coronary angiography, and presence of ≥ 2 myocardial segments with reversible perfusion defects (RPDs) identified by SPECT myocardial perfusion scan.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carvalho et al published data from Brazil in 2014 [ 16 ]. Patients were included with exertional CP, normal coronary angiography, and presence of ≥ 2 myocardial segments with reversible perfusion defects (RPDs) identified by SPECT myocardial perfusion scan.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed a 14% increase in oxygen uptake and were able to show a significant reduction in myocardial ischemia on SPECT (SDS, summed difference score). There was a significant improvement of the SF-36 scores in all categories but general health status [ 16 ]. In a further study, Carvalho et al compared the same patient population with a healthy control group in regard to left ventricular ejection fraction (LVEF) at peak exercise on radionuclide ventriculography [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] A cardiac rehabilitation program has been shown to improve symptoms, psychological well-being, and cardiovascular risk factors in women with microvascular angina. [79, 80]…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Aqui, torna-se oportuno observar que as fronteiras classificatórias das várias etiologias possíveis no conundrum da doença miocárdica isquêmica microvascular são relativamente tênues. Isso é patente quando se observa que, mesmo em trabalho desta Instituição, focalizando grupo rotulado como composto por pacientes com isquemia microvascular primária, vários pacientes apresentavam fatores como esses acima mencionados(Carvalho et al, 2015; fato de 50% dos pacientes investigados estarem em uso regular de AAS antes do início do protocolo também poderia ser fator de confusão. No entanto, ao se comparar os pacientes com ou sem uso prévio de AAS, não foi constatada diferença, pois o SDS manteve-se significativamente menor ao final do tratamento em ambos os grupos.A presença de hipertrofia de ventrículo esquerdo (HVE), definida como índice de massa de VE acima do valor de normalidade em ECO de repouso, foi constatada em 8 indivíduos (32%).…”
unclassified